Examples of acquisition and application of biooptical signals - Cysewska-Sobusiak, Anna Romana (Photonics Letters of Poland, 2019)
Scientific activity of Division of Metrology and Optoelectronics with Poznan University of Poland (PUT) includes methods and systems used in modern electronic, optoelectronic, and biomedical metrology. Noninvasive diagnostic methods applied in medical engineering, with special interest in optoelectronic sensor technology and advanced methods of imaging, are considered in the paper. The author who was the Head of the Division presents the short review of some selected former results of studies related to biophotonics. Full Text: PDF References A. Cysewska-Sobusiak, "Powers and Limitations of Noninvasive Measurements Implemented in Pulse Oximetry", Biocybernetics and Biomedical Engineering 22 (2002). DirectLink J.G. Webster, Design of pulse oximeters (Bristol, IOP Publishing Ltd 1997). CrossRef T. Aoyagi, "Pulse oximetry: its invention, theory, and future", Journal of Anesthesia 17, 4 (2003). CrossRef A.A. Alian and K.H Shelley, "Photoplethysmography", Anesthesiology 28, 4 (2014). CrossRef F.A. Duck, Physical properties of tissue: a comprehensive reference book (San Diego, Academia Press 1990). CrossRef Z. Krawiecki, A. Cysewska-Sobusiak, G. Wiczyński, and A. Odon, "Modeling and measurements of light transmission through human tissues", Bull. Pol. Ac. Tech. 56, 2 (2008). DirectLink A. Cysewska-Sobusiak, "One-dimensional representation of light-tissue interaction for application in noninvasive oximetry", Opt. Eng. 36, 4 (1997). CrossRef D. Prokop, A. Cysewska-Sobusiak, and A. Hulewicz, "Monitoring of the Arterial Blood Waveforms with a Multi-Sensor System", Procedia Eng. 47 (2012). CrossRef A. Cysewska-Sobusiak, P. Skrzywanek, and A. Sowier, "Utilization of Miniprobes in Modern Endoscopic Ultrasonography", IEEE Sensors Journal 6, 5 (2006). CrossRef A. Cysewska-Sobusiak, G. Wiczyński, Z. Krawiecki, and A. Sowier, "Role of optical techniques in combined use of selected methods of medical imaging", Opto-Electron. Rev. 16, 2 (2008). CrossRef A. Cysewska-Sobusiak, M. Bołtrukiewicz, and J. Parzych, "Evaluation of fluorescence images acquired from oligonucleotide libraries", Optica Applicata 38, 2 (2008). <a class="file" href="https://yadda.icm.edu.pl/baztech/element/bwmeta1.element.baztech-article-BPW9-0006-0062?q=bwmeta1.element.baztech-volume-0078-5466-optica_applicata-2008-vol__38_nr_2;8&qt=CHILDREN-STATELESS" target="_parent"> DirectLink M. Jukiewicz and A. Cysewska-Sobusiak, "Stimuli design for SSVEP-based brain computer-interface", Intl. Journal of Electronics and Telecommunications 62, 2 (2016). CrossRef G. Wiczyński, "Inaccuracy of Short-Term Light Flicker Pst Indicator Measuring With a Flickermeter", IEEE Trans. on Power Delivery, 27, 2 (2012). CrossRef A. Hulewicz, "A New Approach to Objective Evaluation of Human Visual Acuity", Phot. Lett. Poland 6, 4 (2014). CrossRef A. Zielińska, K. Kiluk, M. Wojtkowski, and K. Komar, "System for psychophysical measurements of two-photon vision", Phot. Lett. Poland 11, 1 (2019). CrossRef